1978
DOI: 10.1021/bi00612a025
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance studies of inorganic phosphate binding to yeast inorganic pyrophosphatase

Abstract: Yeast inorganic pyrophosphatase is a dimer of identical subunits. Previous work (Rapoport, T.A., et al. (1973) Eur. J. Biochem. 33, 341) indicated the presence of two different Mn2+ binding sites per subunit. In the present work, the binding of inorganic phosphate to the Mn2+-inorganic pyrophosphatase complex has been studied by 1H and 31P nuclear magnetic resonance. Two distinct phosphate sites have been found, having dissociation constants of 0.24 mM and 18 mM. The Mn2+-31P distance from tightly bound Mn2+ t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
5
19
0
Order By: Relevance
“…The 2.35 A structure of the yeast PPase*Mn3Pi2 complex (Chirgadze et al, 1991) showed that the geometry at the metal ions is distorted octahedral. The ligands to the three divalent cations are mainly Glu, Asp, and phosphate, and the phosphate ions have different occupancies, consistent with 31P nuclear 0006-2960/95/0434-782$09.00/0 © 1995 American Chemical Society magnetic resonance data (Hamm & Cooperman, 1978).…”
supporting
confidence: 66%
“…The 2.35 A structure of the yeast PPase*Mn3Pi2 complex (Chirgadze et al, 1991) showed that the geometry at the metal ions is distorted octahedral. The ligands to the three divalent cations are mainly Glu, Asp, and phosphate, and the phosphate ions have different occupancies, consistent with 31P nuclear 0006-2960/95/0434-782$09.00/0 © 1995 American Chemical Society magnetic resonance data (Hamm & Cooperman, 1978).…”
supporting
confidence: 66%
“…PPase has both high-and low-affinity sites for P¡ (Hamm & Cooperman, 1978;Cooperman et al, 1981;Springs et al, 1981;Welsh et al, 1983). Thus, at relatively high P¡ concentrations, the total enzyme concentration is given by eq 3,…”
Section: Resultsmentioning
confidence: 99%
“…We propose that it is the high lability of Mg2+-oxygen bonds which accounts for the rapid product release found in the presence of Mg2+. That M2+-oxygen bonds are broken during product release is suggested by the following observations: first, one or two divalent metal ions per subunit are taken up and released during a complete turnover (eq 1 and 2); second, NMR chemical shifts of 113Cd2+ bound to PPase are characteristic of predominant, if not exclusive, oxygen ligand environments (Welsh et al, 1983); third, the effects of Mn2+ (Hamm & Cooperman, 1978) and 113Cd2+ (Welsh et al, 1983) on enzyme-bound [32P]P¡ NMR show that there is inner-sphere M2+ coordination to P¡ bound in the high-affinity site and outer-sphere coordination to the second P¡ bound in the lowaffinity site. That Mg2+-0 ligand bonds should be particularly labile is suggested by the distinctly weaker complexes that Mg2+, as compared with Zn2+, Co2+, and Mn2+, forms with oxygen ligands (Table VII).…”
Section: Discussionmentioning
confidence: 99%
“…The high yields of derivatized peptides obtained in this work suggest the potential general utility of our procedure for locating arginine residues derivatized with phenylglyoxal within the covalent structure of proteins. derway.2 In addition, a fair amount is known about the stoichiometries and affinities of divalent metal ion, pyrophosphate and phosphate binding ; Cooperman & Chiu, 1973a;Rapoport et al, 1973; Hamm & Cooperman, 1978;D. J. Hamm, B. Springs, and B. S. Cooperman, unpublished experiments), about the kinetic and chemical mechanisms (Rapoport et al, 1972; Moe & Butler, 1972;Konsowitz & Cooperman, 1976; Hackney & Boyer, 1978), about the orientation of metal ions and phosphate ligands at the active site (Hamm & Cooperman, 1978), and about the identity and roles of essential amino acid residues (Cooperman & Chiu, 1973b; Heitmann & Uhlig, 1974).…”
mentioning
confidence: 99%